A computable general equilibrium assessment of a developing country joining an Annex B emission permit market - Claudia Kemfert; Hans Kremers (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
During the last years, the developing regions have come under increased pressure by the developed countries, in particular the USA, to join the international effort in global greenhouse gas abatement. On the one hand, the participation of the developing regions would offer the developed world with low cost opportunities for abatement. On the other hand, the economies of some developed regions such as China and India exhibit such fast growth that they are expected to be responsible for a significant part of future emissions during the next decade. The latter regions object to the imposition of emission targets on their economy as it would significantly hamper their economic growth. This paper focusses on the consequences of certain proposals to set emission targets for developing countries, here China. One of these proposals follows the USA by letting China accept its projected ?Business-as-Usual? emission level for 2012 as its target. A proposal by the Center for Clean Air Policy takes more consideration for the viewpoint of the developing countries by imposing a so-called ?growth-baseline? for China, where a target is set on its emission efficiency.
Keywords: 330